The Effect of Calcium-D Supplementation on Glucose Control of Patients with Gestational Diabetes - Ghanbari 1, Setareh; Kohbodi 2, Mina Sadat; Zolfaghari 3, Pouneh; Mahdavian 4, Maryam; Sohrabi 5*, Mohammad Bagher (Shahroud Journal of Medical Sciences, 2020)
Background: Gestational diabetes (GDM) is a complication of pregnancy that is characterized by intolerance to carbohydrates and metabolic diseases. Gestational diabetes has many maternal and fetal complications that need to be carefully controlled. Therefore, the aim of the present study was to investigate the effect of calcium-D supplementation on glucose control of patients with gestational diabetes.Methods: This randomized clinical trial study was performed on 84 pregnant women with GDM. Some inclusion criteria included a positive one-step test during the 24th-28th week of pregnancy and definitive diagnosis of GDM and some exclusion criteria including patients with a previous history of diabetes who required insulin therapy during the intervention. The intervention group were given routine treatment and calcium supplements plus vitamin D and the control group were given routine treatment only. Fasting blood glucose was measured monthly in both groups until the end of pregnancy. All analyses were performed using SPSS software version 16 and related tests like mean± SD, chi-square test and multivariate logistic regression. Significant level was set at 0.05.Results: Of the 84 patients examined, the mean age was 29.4±5.2 years old and there were no significant differences between the two groups (Pvalue= 0.189). The mean BMI of all patients was 25.31±2.72 kg/m2 and there was no significant difference between the two groups (Pvalue= 0.312). The mean of the FBS level at the end of the study in the case group was 91.5±12.9 mg/dl and in the control group it was 98.9±15.8 mg/dl, which was significantly lower in the case group (p=0.014). GDM variables were significantly associated with a positive history of diabetes mellitus (Pvalue<0.033), previous history of GDM (Pvalue<0.013) and FBS (Pvalue<0.001) and there was no significant relationship with other variables.Conclusions: The results of this study showed that calcium-D supplementation has a significant effect on glucose control in patients with GDM and its use is recommended in these patients. Keywords: Gestational diabetes, Calcium, Vitamin D, Glucose.